CD4+ T cell recognition of HIV-1 alternate reading frame proteins - Sop, Joel; Beckey, Tyler P.; Blankson, Joel N. (Frontiers in Immunology, 2025)
HIV-1 alternative reading frame proteins (ARFPs) have been shown to elicit CD8+ T cell responses, but less is known about the recognition of these proteins by CD4+ T cells. In this study, we analyzed responses of CD8-depleted peripheral blood mononuclear cells from chronic progressors (CPs) on suppressive antiretroviral therapy to ARFP peptide pools derived from HIV Gag, polymerase (Pol), and envelope (Env) proteins. Memory CD4+ T cell responses were detected to Gag ARFP peptide pools in 7 out of 13 CPs and to Env ARFP peptide pools in 2 out of 13 CPs. Individual peptide stimulation identified immunogenic peptides that were predicted to bind to major histocompatibility complex class II (MHC-II) proteins. HIV RNA was detected in culture supernatants from 3 of 6 CPs following stimulation of CD4+ T cells with ARFP peptide pools. These findings demonstrate that ARFP-derived peptides elicit antigen-specific CD4+ T cell responses and may contribute to latency reversal. Our data expand the known HIV immunopeptidome and suggest that ARFPs may serve as potential targets for immune-based interventions.